Counseling Independent Curriculum for Middle School Sundanese Language Teachers in Bandung City - Nunuy Nurjanah; Yayat Sudaryat; Rostika Srihilmawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Participants in the Implementation of the Service Program are junior high school teachers in the Bandung City Education Office Area. The number of participants who attended online was approximately 100 people while those offline were 10 people. Counseling is related to six things: (1) Independent Curriculum; (2) Sundanese Local Content Subjects; (3) Sundanese Language Learning Foundation; (4) Learning Outcomes of Sundanese Language Subjects; (5) Flow of Learning Objectives; (6) Teaching Module. The steps for implementing the service consist of (1) the preparation stage which includes initial observations, (2) the implementation stage which includes the entire series of extension activities and (3) the evaluation stage, relating to the participants, time and service material (including the overall counseling implementation report). The results of the service program in the form of counseling are based on the results of the pretest and posttest carried out for PKM participants.